Protection of nonmodified phage lambda against EcoK restriction mediated by recA protein - Koukalová, B; Kuhrová, V; Reich, J (Folia microbiologica, 1985)
A study was conducted to establish whether the EcoK-specific restriction, which is alleviated in E. coli cells after UV induction of the SOS response (Day 1977), is also alleviated under the influence of an increased level of recA protein without induction of other SOS functions. The host cells used were E. coli K-12, strain AB2497, and its derivatives; the nonmodified phage lambda was a mutant b2b5(vir). An increase of the recA protein level was induced using the plasmid pX02, which is a recombinant of pBR322 carrying the recA gene of E. coli. AB2497(pX02) cells were found to exhibit a lower level of restriction than those without plasmid. The results indicate that the recA protein protects phage DNA during the process of restriction. A further factor affecting restriction is the growth phase of the culture of the restricting host: cells in the late stationary phase exhibit lower restriction than those in the exponential phase of growth. By a combination of these two factors (presence of plasmid pX02 and stationary growth phase) one can reduce the restriction of nonmodified phage about 300 times.
Keywords: Bacteriophage lambda; Rec A Recombinases; plazmidy; DNA virů; Escherichia coli; bakteriofág lambda; Plasmids; DNA, Viral; RecA-rekombinasy